CD4-binding regions of human immunodeficiency virus envelope glycoprotein gp120 defined by proteolytic digestion. - Pollard, S R (1991)
The gp120 envelope glycoprotein of human immunodeficiency virus type 1 binds the cell surface protein CD4 with high affinity. Here we report the use of proteolysis to define regions of gp120 involved in CD4 binding. Cleavage of gp120 with Staphylococcus aureus V8 protease at residue 269 or with trypsin at residue 432 destroys CD4 binding. These same sites are protected from proteolytic cleavage by bound CD4. Cleavages at 64, 144, 166, 172, and 315 do not affect binding and are not protected by bound CD4, indicating that these regions are not critical for binding CD4. All proteolytic fragments found in coprecipitates with CD4 were covalently associated via disulfides and comprised complete gp120 molecules. Previous conclusions by Nygren et al. [Nygren, A., Bergman, T., Matthews, T., Jornvall, H. & Wigzell, H. (1988) Proc. Natl. Acad. Sci. USA 85, 6543-6546] that both large and small (95-kDa and 25-kDa) V8 proteolytic fragments bind CD4, independently, are not distinguished by their experiments from the result found here that the small fragment immunoprecipitates with CD4 while disulfide-linked to the larger fragment.